2013
DOI: 10.1177/0143831x13501004
|View full text |Cite
|
Sign up to set email alerts
|

Institutions, unionization and voice: The relative impact of context and actors on firm level practice

Abstract: Trade unions provide a voice in the way firms are run, an input into reward systems and increased security of employment. But these vary with national context. Using transnational survey evidence, we explore the relative impact of setting, and of unions and collective bargaining, on these issues. We find that, irrespective of context organisations are significantly more likely to make usage of compulsory redundancies in the absence of unions and collective bargaining. However, in other areas, the impact of uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 62 publications
0
29
0
3
Order By: Relevance
“…Indeed, despite increasing levels of internationalization and attendant pressures to de-regulate economies, in general, and employment regulations, in particular, comparative institutional analysis (CIA) has shown how patterns of economic coordination continue to differ between countries (Hotho, 2014;Psychogios and Wood, 2010;Szamosi et al, 2010), supporting the view that contrasting institutional settings lead to different kinds of advantages to firms (Allen and Whitely, 2012;Schneider and Paunescu, 2012). More specifically, CIA analyses have shown how employment legislation can shape employers' investments in particular employee skills (Harcourt and Wood, 2007), how institutionalized forms of worker voice can lower employee turnover rates (Croucher et al, 2012) and collective redundancies (Brewster et al, 2015), and how institutions shape organizations' use of external training providers (Walker et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…Indeed, despite increasing levels of internationalization and attendant pressures to de-regulate economies, in general, and employment regulations, in particular, comparative institutional analysis (CIA) has shown how patterns of economic coordination continue to differ between countries (Hotho, 2014;Psychogios and Wood, 2010;Szamosi et al, 2010), supporting the view that contrasting institutional settings lead to different kinds of advantages to firms (Allen and Whitely, 2012;Schneider and Paunescu, 2012). More specifically, CIA analyses have shown how employment legislation can shape employers' investments in particular employee skills (Harcourt and Wood, 2007), how institutionalized forms of worker voice can lower employee turnover rates (Croucher et al, 2012) and collective redundancies (Brewster et al, 2015), and how institutions shape organizations' use of external training providers (Walker et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…It is expected that employees will have least voice in the owner-focused LMEs and more in the stakeholder-focused CMEs. There is now considerable evidence that these predictions are broadly correct Brewster et al 2014;Brewster, Wood, and Goergen 2015). Brewster et al (2014) found that, although the picture was complex, both direct and indirect participation varied with setting, being much more likely to occur in CMEs.…”
Section: Employer-employee Communicationmentioning
confidence: 99%
“…The comparative capitalisms literature argues that there is a limited range of institutional factors that shape the choices of rational actors, creating path dependency (Goergen et al, 2012), and that these institutional factors, such as law and political systems, interact with each other to have a combined effect on HRM (Psychogios & Wood, 2010). Empirical examples include the use of non-standard working time across market economies (Richbell et al, 2011), levels of voluntary and involuntary employee turnover (Croucher et al, 2012), use of a broad range of HRM practices (Farndale et al, 2008), and extent of union recognition (Brewster et al, 2015b). The notion of complementarities is again key here, whereby complex patterns of institutional factors combine to create similar HRM outcomes (Croucher et al, 2012;Walker et al, 2014).…”
Section: Levels/units Of Analysismentioning
confidence: 99%